Population Pharmacokinetics and Exposure–Safety Relationship of Paclitaxel Liposome in Patients With Non-small Cell Lung Cancer - Zhou, Haiyan; Yan, Jiaqing; Chen, Wei; Yang, Jun; Liu, Min; Zhang, Yuan; Shen, Xin; Ma, Yinglin; Hu, Xingsheng; Wang, Yan; Du, Kehe; Li, Guohui (Frontiers in Oncology, 2021)
Purpose Paclitaxel liposome (Lipusu) is a firstly commercialized liposomal formulation of paclitaxel. Data on the pharmacokinetics of paclitaxel liposome were seldom reported especially in patients. This study aimed to build a population pharmacokinetic model and further explore the exposure-safety relationship for paclitaxel liposome in patients with non-small cell lung cancer. Methods Data from 45 patients with a total of 349 plasma concentrations were analyzed. The population pharmacokinetic model was built by nonlinear mixed effect modeling technique. Results The pharmacokinetics of paclitaxel liposome was well described by a three-compartment model with first-order elimination. For the dose of 175mg∙m-2, the estimated clearance of total plasma paclitaxel was 21.55 L∙h-1. Age, sex, body weight, total bilirubin, albumin, serum creatinine, and creatinine clearance did not influence the paclitaxel pharmacokinetics. The exposure to paclitaxel had no significant change in the presence of traditional Chinese medicine aidi injection. The exploratory exposure-safety relationship was well described by a generalized linear regression model. Higher probabilities of grade >1 neutropenia were observed in patients with higher exposure to paclitaxel. Conclusion This population pharmacokinetic model adequately described the pharmacokinetics of paclitaxel liposome in patients with non-small cell lung cancer. Predicted exposure of paclitaxel did not change in the presence of traditional Chinese medicine aidi injection. The exposure-safety analysis suggested that a higher risk of neutropenia was correlated with higher exposure to paclitaxel.